A Late-time Radio Survey of Type Ia-CSM Supernovae with the Very Large Array - Griffith, Olivia; Showerman, Grace; Sarbadhicary, Sumit K.; Harris, Chelsea E.; Chomiuk, Laura; Sollerman, Jesper; Lundqvist, Peter; Moldón, Javier; Pérez-Torres, Miguel; Kool, Erik C.; Moriya, Takashi J. (Institute of Physics Publishing, 2026)
Type Ia-CSM supernovae (SNe) are a rare and peculiar subclass of thermonuclear SNe characterized by emission lines of hydrogen or helium, indicative of high-density circumstellar medium (CSM). Their implied mass-loss rates of ∼10−4–10−1 M⊙ yr−1 (assuming ∼100 km s−1 winds) from optical observations are generally in excess of values observed in realistic SN Ia progenitors. In this paper, we present an independent study of CSM densities around a sample of 29 archival Ia-CSM SNe using radio observations with the Karl G. Jansky Very Large Array at 6 GHz. Motivated by the late (∼2 yr) radio detection of the Ia-CSM SN 2020eyj, we observed old (>1 yr) SNe, when we are more likely to see the emergent synchrotron emission that may have been suppressed earlier by free–free absorption by the CSM. We do not detect radio emission down to 3σ limits of ∼35 μJy in our sample. The only radio-detected candidate in our sample, SN 2022esa, was likely misclassified as a Ia-CSM with early spectra, and appears more consistent with a peculiar Ic based on later epochs. Assuming wind-like CSM with temperatures between 2 × 104 K and 105 K, and a magnetic field-to-shock energy fraction B = 0.01 − 0.1, the radio upper limits rule out mass-loss rates between ∼10−4 and 10−2 M⊙ yr−1 (100 km s−1)−1. This is somewhat in tension with the estimates from optical observations, and may indicate that more complex CSM geometries and/or lower values of B may be present.